Pinisi Maritime Traditions in The Bonto Bahari Community of Bulukumba - Lisnayanti, Lisnayanti; Rahmat,; Mastanning, (Al-Hikmah, 2024)
This research aims to examine the elements of Islamic culture in the pinisi maritime tradition of the Bonto Bahari Bulukumba community. Pinisi boat, which originated from the Sawerigading story, is a traditional boat from South Sulawesi, precisely Bulukumba, known as Butta Panrita Lopi. Pinisi in its manufacture is still thick with the culture of the local community. In its development, the pinisi boat has been recognized as a humanitarian heritage for intangible culture authorized by UNESCO. This research is a cultural research using qualitative data obtained from field study data and literature data. The data collection methods used are interviews, observations, and through written documents. The results of this study show that in the tradition of pinisi maritime there are several rituals performed, namely, annakbang kalabiseang (keel cutting), annattara (keel connection), appasili (rejecting bad luck), ammossi (cutting the navel), and annyorong lopi (boat launching). The elements of Islamic culture contained in these rituals are religious system and religious ceremonies, community organization system, and livelihood system.